Cigarette Tow Newsletter (Tufts Archival Research Center, 2007)
1965 Cigarette Tow Newsletter, featuring analysis of trends in the tobacco industry, clippings regarding worldwide tobacco companies, listings of new tobacco products worldwide, and patents issued. Provides commentary on domestic cigarette production and consumption, smoking and health, foreign cigarette production and consumption, and new brands. Discusses cigarette labeling bill and trends in excise taxes. Cites Dr. John Gibbon in that "cigarettes do not cause cancer."